76.8k views
0 votes
Divide: (x3-1) by (x-1 )
plz divide ....​

User Cristian M
by
4.9k points

2 Answers

3 votes

Answer:


\frac{ {x}^(3) - 1}{x - 1} \\ = \frac{ {x}^(3) - {1}^(3) }{x - 1} \\ = > but : {(x - 1)}^(3) = (x - 1)( {x}^(2) - 2x + 1) \\ \therefore \: = \frac{(x - 1)( {x}^(2) - 2x + 1) }{(x - 1)} \\ = {x}^(2) - 2x + 1 \\ = {(x - 1)}^(2)

User Shaun Ryan
by
5.2k points
5 votes


\frac{ {x}^(3) - 1 }{ x- 1} \\ = \frac{ {x}^(3) - 1 }{x - 1} \\ = \frac{( {x} - 1)( {x}^(2) + x + 1) }{x - 1} \\ </p><p>= {x}^(2) +x+1

User Vlasits
by
5.1k points